STRATEGI PEMBELAJARAN HEURISTIK PADA SISWA KELAS 5 MI TAMBAKSARI BLORA - Siti Nur'aini (Sekolah Tinggi Agama Islam Muhammadiyah Blora, 2022)
Heuristic learning is a learning strategy that requires students to be active, namely trying to know and find their own problems presented by the teacher by using their prior knowledge and experience. Heuristic learning is one of the learning strategies that can be chosen and used by teachers in learning activities. Heuristic learning is an effort to realize learning activities that are conducive, effective, and efficient, namely students feel happy to learn, and there is active interaction between students and teachers, and between students and students. Through conducive, effective, and efficient learning activities, it is expected to lead to optimal learning achievement in students. Heuristic learning is expected to make great progress towards developing attitudes, values, and behaviors that allow students to actively participate in learning activities. In terms of the benefits of heuristic learning, it should be a valuable guideline for teachers. This means that teachers can apply it well in the learning activities carried out, so that efforts to encourage motivation, instill learning understanding, and form active learning students can be embedded properly. Keywoards: Heuristic learning strategy